Return and Risk Analysis on Cryptocurrency Assets - Sakina Ichsani; Nugroho Satya Mahendra (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to analyze the return and risk of Cryptocurrency assets in order to find out which crypto assets have small risks and large returns. In this research, the test procedures used were the Kruskal Wallis test and paired sample t-test. The research time span was obtained from January 1, 2019 to December 31, 2021 as well as the time span for data collection for price comparisons before and during the COVID-19 pandemic for 2 months from march 11, 2020. The results of this research are that bitcoin, ethereum, and dogecoin do not have a significant return comparison, for the results of risk research also have the result that there is no significant risk comparison between bitcoin, ethereum, and dogecoin. After that, for the results of the price comparison of bitcoin, ethereum, and dogecoin before the covid-19 pandemic and after the announcement of the covid-19 pandemic, the result is bitcoin and ethereum has a significant comparison between the time before the covid-19 pandemic and after the announcement of covid-19. On the contrary, dogecoin did not face a significant price comparison before the covid-19 pandemic as well as after the announcement of covid-19. Before starting an investment, it is better to look at the ability of Cryptocurrency assets to minimize risks and make sure whether the investment objectives are for the long and short term.